Por uma sociologia da suspensão: ensino de sociologia e narrativas de si como dispositivo de formação - Röwer, Joana Elisa (2016)
This doctoral thesis refers to the didactic of Sociology in High School. It is about knowing how the sociological imagination, the estrangement, and the denaturalization, put as the objectives of Sociology in High School, approach the autobiographical narratives as formation devices. It started from thehypothesis that the narration of our own experience provokes estrangements and denaturalization, ofknowledge of common sense and enable awareness of the relations between History, social structure, andindividual trajectories. The objectives were: to put in dialogue the legal orientations about the specifics ofSociology and the biographical narratives, seen as formation devices; to debate the epistemologicalfoundation of the work with self-referential narratives in Sociology classes; to advocate that this type ofnarrative can generate estrangements/denaturalization and incite (re)ordination of the world, attribution ofsense and self-consciousness. A dialogue was initiated about the concepts of (auto)biographical researchin Education (DELORY-MOMBERGER, 2012; JOSSO, 2010; PASSEGGI, 2011; PINEAU, 2012;SOUZA, 2006); the concept of sociological imagination (BERGER, 2011; MILLS, 1975), its effect of“self-analysis” (BOURDIEU, 1997, 2012), the development of fundamental intellectual habits (LAHIRE,2014), the concepts of estrangement/denaturalization (DA MATTA, 1978; VELHO, 1978); and, theresearches about Sociology in school (OLIVEIRA, 2011; SILVA, 2005). The work was accomplishedthrough qualitative and quantitative research, bibliographic, documental, and field research, withintervention when proposing and analyzing a teaching methodology in Sociology. The analysis focused on the absence of didactic-methodological foundation in the legal orientations about Sociology in HighSchool (DCNEM, 2012; OCN, 2006; PCN, 1999; State curricular guidelines, Sociology lesson plan), with regards to self-awareness; the necessity and possibility of sociological interlocutions of the autobiographical narratives as formation devices; and, the feasibility of the use of narratives, produced inclass, to engender estrangements, denaturalization and consciousness. The teaching proposal presentedand developed had as principles: (1) The conception of socialized individual, (2) The education as anexperience; (3) The relation of the social with the individual in the centrality of the teaching of socialsciences/sociology and the estrangement and the denaturalization understood as epistemologicalprinciples of Sociology; and (4) The relation between knowledge, sense, and the construction of self,pointed out by Josso (2010); the autobiographical reflexivity highlighted by Passeggi (2011); and, therelation between biography and learning from Delory-Momberger (2006, 2012, 2014). The teachingproposal of sociology with self-referential reports resulted in: (1) The denaturalization as condition for theconstruction and reconstruction of the experience; (2) Self-estrangement by the reflexivity andestrangement of the other; (3) Importance of a subject that leads to reflection; (4) Reflection aboutprejudice as the result of estrangement and denaturalization; (5) The consciousness of self as an individual that builds itself amid the social-cultural constraints has proved to be an element of dispositionfor learning, for the reconstruction of experience; and, (6) Individualized and individualizing perceptionof self-construction resulted in no disposition/opening for other reflections and/or possibilities fordifferent perceptions of the self and of others. Thus, the work here presented advocates the biographicalapproach as a formation device as a possibility for construction of space/time of production of theestrangement and of the denaturalization through the relation with sociological themes. The relationbetween life stories and the teaching of sociology configures as a possibility of suspension of knowledgeand learning of contents as well as of the other in relation to self.